2012
DOI: 10.1016/j.jjcc.2012.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Atrioventricular block in patients with thyroid dysfunction: Prognosis after treatment with hormone supplementation or antithyroid medication

Abstract: AV block associated with thyroid dysfunction needs great attention regardless of type of the thyroid disease. Patients with II and/or III degree AV block in the setting of thyroid dysfunction almost always need permanent pacemaker insertion even after normalization of thyroid status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 20 publications
(23 reference statements)
0
21
0
1
Order By: Relevance
“…16 In other studies, AV block was explained by a different factor such as electrolyte imbalance (hypercalcaemia, hypokalaemia), infection, or digoxin administration. [17][18][19][20][21][22] There is a wide spectrum of potential aetiologies of complete AV block, 23 but in our case clear triggering factor other than thyrotoxicosis was not detected. Mildly abnormal laboratory results were not able to explain AV block.…”
Section: Discussionmentioning
confidence: 70%
“…16 In other studies, AV block was explained by a different factor such as electrolyte imbalance (hypercalcaemia, hypokalaemia), infection, or digoxin administration. [17][18][19][20][21][22] There is a wide spectrum of potential aetiologies of complete AV block, 23 but in our case clear triggering factor other than thyrotoxicosis was not detected. Mildly abnormal laboratory results were not able to explain AV block.…”
Section: Discussionmentioning
confidence: 70%
“…Myxedema coma requiring temporary or permanent pacemaker implantation is rare, and the requirement of the procedure is mainly due to second‐degree or complete AV block. Although those conditions usually need permanent pacemaker insertion even after normalization of thyroid status, reversible cases have been reported . To cite an example, Waseem et al reported a case of myxedema coma with severe bradycardia and high‐grade AV block that was successfully treated with thyroxine hormone replacement without requiring cardiac pacemaker placement .…”
Section: Discussionmentioning
confidence: 99%
“…Coexistent infection, hypercalcaemia and concurrent drug use have also been implicated as contributory factors to AV block in these patients 3. Beta-adrenoceptor antagonists, which form standard treatment for symptomatic tachycardia in paediatric hyperthyroidism,4 block sympathetic stimulation to both the sinoatrial and AV nodes.…”
Section: Discussionmentioning
confidence: 99%